2006
DOI: 10.1381/096089206778663643
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Factors for Rhabdomyolysis after Bariatric Surgery

Abstract: After surgery for obesity, the risk of RML increases with prolonged surgery (>4 hours) and in diabetic obese patients with BMI >40 kg/m(2). In such patients, CK could be systematically measured to verify the presence of muscle injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 20 publications
7
73
1
6
Order By: Relevance
“…In a prospective cohort study involving 49 obese patients undergoing bariatric surgery, the authors described prolonged surgery (more than four hours), extreme surgical positions, ASA physical status III-IV, and Preop = preoperative; PO = postoperative; POD = postoperative day; Hb = hemoglobin; CK = serum creatinine kinase the presence of diabetes or hypertension as risk factors associated with development of RML. 6 These findings confirm earlier studies in animals that showed the occurrence of myonecrosis when an intracompartmental pressure of 30 mmHg was applied for four to eight hours. 9 The previous reports of RML described its occurrence in bariatric surgery involving mainly muscles of the gluteal region, as these procedures were performed in the supine position over a lumber pad.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In a prospective cohort study involving 49 obese patients undergoing bariatric surgery, the authors described prolonged surgery (more than four hours), extreme surgical positions, ASA physical status III-IV, and Preop = preoperative; PO = postoperative; POD = postoperative day; Hb = hemoglobin; CK = serum creatinine kinase the presence of diabetes or hypertension as risk factors associated with development of RML. 6 These findings confirm earlier studies in animals that showed the occurrence of myonecrosis when an intracompartmental pressure of 30 mmHg was applied for four to eight hours. 9 The previous reports of RML described its occurrence in bariatric surgery involving mainly muscles of the gluteal region, as these procedures were performed in the supine position over a lumber pad.…”
Section: Discussionsupporting
confidence: 90%
“…9 The previous reports of RML described its occurrence in bariatric surgery involving mainly muscles of the gluteal region, as these procedures were performed in the supine position over a lumber pad. 6 Our patient developed RML involving shoulder girdle muscles and upper arms probably due to morbid obesity, maintenance of a 15°Trendelenburg position over six hours, and prolonged unrelieved pressure by excessive fat over shoulder girdle and upper arm muscles. The occurrence of microangiopathy with increased platelet aggregation and altered arteriolar permeability as seen in diabetic patients could have increased the risk of muscular ischemia in our patient.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…There are also other factors that are discussed to lead to CK rise. While the influence of obesity remains controversial 3,14 , superobesity is regarded as major risk factor in literature 14,19 . However, neither obesity (BMI>25 kg/m2) nor super-obesity (BMI>30 kg/m2) showed influence on CK levels in our study.…”
Section: Other Reasons For Ck Rise In the Literaturementioning
confidence: 99%
“…During prolonged surgery, diffuse local muscle compression with ischemia and subsequent reperfusion injury is inevitable, despite utilization of modern operating tables and padding 9,10 . Different manifestations after various surgical procedures ranging from simple serum CK rise to rhabdomyolysis with complex organ failure have been reported in literature 4,8,[11][12][13][14] . With limited direct surgical trauma to the musculature during craniotomies, we hypothesize that postoperative CK excess is, among other factors, related to patient positioning.…”
Section: Introductionmentioning
confidence: 99%